2006
DOI: 10.1111/j.1570-8703.2006.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of female melon fly, Bactrocera cucurbitae, to host‐associated visual and olfactory stimuli

Abstract: In a series of studies conducted in Hawaii under seminatural conditions, we quantified the response of sexually mature, host‐seeking female melon flies, Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae), to different types of visual and chemical host‐associated stimuli with the main aim of developing a monitoring device for females. Experiments were conducted using Tangletrap‐coated fruit mimics of either spherical (8 cm diameter) or cylindrical (4.3 cm diameter; 15 cm length) shapes coated with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…Bactrocera cucurbitae is a multivoltine and polyphagous fruit fly that attacks more than 125 cucurbits and solanaceous plant species (Dhillon et al 2005;Pinero et al 2006), grown by small and marginal farmers in the developing countries for essential dietary components and daily livelihood. Melon fly is though one of the most studied fruit fly species in terms of its biology, distribution, quarantine, ecology, behaviour, management and control, owing to its wide distribution, highly invasive nature and importance as an agricultural pest; but still continues to cause significant damage in tropical countries ranging between 30 and 100 %, depending on the plant species and the season (Dhillon et al 2005;Fabre et al 2009;Mwatawala et al 2009;Vayssieres et al 2007Vayssieres et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Bactrocera cucurbitae is a multivoltine and polyphagous fruit fly that attacks more than 125 cucurbits and solanaceous plant species (Dhillon et al 2005;Pinero et al 2006), grown by small and marginal farmers in the developing countries for essential dietary components and daily livelihood. Melon fly is though one of the most studied fruit fly species in terms of its biology, distribution, quarantine, ecology, behaviour, management and control, owing to its wide distribution, highly invasive nature and importance as an agricultural pest; but still continues to cause significant damage in tropical countries ranging between 30 and 100 %, depending on the plant species and the season (Dhillon et al 2005;Fabre et al 2009;Mwatawala et al 2009;Vayssieres et al 2007Vayssieres et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In field cage tests, D. longicaudata females discriminated between various spheres painted with different colours with yellow as the most attractive colour (Messing and Jang 1992). In the same way, several studies have shown that yellow colour is highly attractive to different species of fruit flies (Katsoyannos 1987;Vargas et al 1991;Drew et al 2003;Piñero et al 2006;López-Guillén et al 2009). For example, C. capitata females were mainly attracted to yellow, followed by red, orange, black, and green spheres, whereas white and blue spheres were the least attractive (Katsoyannos 1987).…”
Section: Discussionmentioning
confidence: 97%
“…McPhail traps baited with mango puree captured more females than visual fruitmimicking sticky traps ('Ladd traps') and equal numbers of females as McPhail traps baited with protein odors. Piñero et al (2006) showed that the addition of cucumber odor strongly enhanced the attractiveness of yellow-colored hemispheres, which indicates that both visual and olfactory stimuli are synergistic in eliciting responses of sexually mature melon fly females.…”
Section: Interactions Among Plant Odors Other Attractants and Trapsmentioning
confidence: 97%
“…(Prokopy and Haniotakis 1975;Hill and Hooper 1984;Vargas et al 1991;Drew et al 2003). Indeed, traps that combine visual and olfactory cues may prove to be the most effective for capturing tephritid fruit fly pests (Prokopy and Economopoulos 1975;Epsky and Heath 1998;Piñero et al 2006). Cornelius et al (2000a) used a mango bait in two commercially available fruit fly traps.…”
Section: Interactions Among Plant Odors Other Attractants and Trapsmentioning
confidence: 98%